The Enhancing French Oral Production Skills Through Digital Media: The Effectiveness of the 'French School TV' YouTube Channel in Secondary Education - Mirza, Mutiara; Soraya, Tengku Ratna (Tamaddun Life, 2024)
This study investigates the effectiveness of the "French School TV" YouTube channel in enhancing the oral production skills of secondary school students learning French at MAS YASPI Medan. Employing a pre-experimental design, 26 students from class X Agama were subjected to a pre-test to assess their initial proficiency in introducing themselves in French. The intervention involved the use of YouTube videos from the "French School TV" channel over two sessions, focusing on self-introduction skills. A post-test was conducted to evaluate the improvement in students' oral production skills. The results demonstrated a significant improvement in the students' performance, with the average score rising from 26.92 in the pre-test to 84.58 in the post-test. Statistical analyses, including the Shapiro-Wilk normality test and paired sample t-test, confirmed the normal distribution of data and the significant difference between pre-test and post-test scores (p-value = 0.000). The N-Gain analysis further validated the intervention's effectiveness, with an average N-Gain score of 0.85, categorizing it as "highly effective." These findings suggest that integrating digital media, specifically YouTube, into the language curriculum can significantly enhance student engagement and learning outcomes. The study highlights the need for modern teaching tools and adequate teacher training to maximize the benefits of digital resources. While the results are promising, further research with larger and more diverse samples is recommended to validate these findings and explore the long-term effects of digital media on various aspects of language learning. The present study implies that the "French School TV" YouTube channel is a highly effective tool for improving the oral production skills of students learning French, offering valuable insights for educators, policymakers, and researchers in the field of language education.